The Moderating Effect of Organisational Culture on the Relationship between Information Technology Capability and Firm Performance: An Empirical Evidence from Lagos State, Nigeria - M. A. Arokodare; O. U. Asikhia; G. O. Makinde (New Innovations in Economics, Business and Management Vol. 7, 2022)
Oil and gas marketing organisations around the world are faced with the challenge of maintaining a greater market share among competitors in the oil and gas industry. Due to organisational culture rigidity and inadequate adoption of information technology competence in their organisations, most business managers in Nigeria’s oil and gas marketing industry find it difficult to consistently achieve increases in performance in terms of market share. As a result, the moderating effect of organisational culture on the link between information technology capacity and performance of oil and gas marketing enterprises in Lagos State, Nigeria, was explored in this study. The survey research design was used in this study. In Lagos State, Nigeria, the target population consisted of 515 oil and gas marketing and retail shops. The method used was entire enumeration. The analysis indicated that there is a significant and positive relationship between information technology capability and market share of oil and gas marketing companies in Lagos State, Nigeria, and that organisational culture significantly moderates the relationship between information technology capability and market share. According to the findings, there is a link between information technology capability and market share. Furthermore, the relationship between information technology competency and market share is moderated by organisational culture.